Trick or treat? a bibliometric literature review of corporate social responsibility and earnings management - Deng, Yang; Ong, Tze San; Senik, Rosmila (John Wiley and Sons Ltd, 2024)
Research Question: This study seeks to examine and synthesize the extant literature to summarize whether the essence of corporate social responsibility (CSR) genuinely stems from an authentic social commitment, or if it primarily serves as a tactic to obscure earnings management (EM) practices. Research Methodology: A systematic literature review methodology is employed to thoroughly assess 75 articles selected from the Web of Science and Scopus databases, integrating bibliometric techniques, and following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Research Findings: Amid evolving economic and social landscapes, the research of the CSR-EM relationship increases, particularly in Asian contexts. Further research found that ESG (environmental, social, and governance) was gradually introduced into the theoretical framework of CSR-EM. However, most of the research does not study the impact of the three dimensions of ESG, respectively. The study concludes the four varied CSR-EM relationships: positive, negative, mixed (depending on EM type), and no correlation, and suggests that this should be determined by both macro (e.g., political and economic environment) and micro determinants (e.g., industries and governance). Therefore, the CSR-EM relationship cannot be simply generalized. At present, most studies study CSR as a whole, and some literature uses CSR disclosure and performance to measure CSR respectively. However, distinctions between CSR disclosure and performance, namely CSR decoupling, remain underexplored. Theoretical and Practical Implications: This review synthesizes four key findings and summarizes seven relevant theories from existing literature, thus enriching the theoretical contributions of CSR-EM research. It underscores the significance of both macro and micro factors on the CSR-EM relationship, introduces the concept of CSR decoupling, and outlines directions for future studies. The review offers insights for policymakers on CSR-EM dynamics and suggests strategies for companies to enhance CSR practices and reporting consistency.